Development and validation of a food photography manual, as a tool for estimation of food portion size in epidemiological dietary surveys in Tunisia. Issue 1 (1st January 2016) - Bouchoucha, Mongia; Akrout, Mouna; Bellali, Hédia; Bouchoucha, Rim; Tarhouni, Fadwa; Mansour, Abderraouf Ben; Zouari, Béchir
Abstract : Background: Estimation of food portion sizes has always been a challenge in dietary studies on free-living individuals. The aim of this work was to develop and validate a food photography manual to improve the accuracy of the estimated size of consumed food portions. Methods: A manual was compiled from digital photos of foods commonly consumed by the Tunisian population. The food was cooked and weighed before taking digital photographs of three portion sizes. The manual was validated by comparing the method of 24-hour recall (using photos) to the reference method [food weighing (FW)]. In both the methods, the comparison focused on food intake amounts as well as nutritional issues. Validity was assessed by Bland–Altman limits of agreement. In total, 31 male and female volunteers aged 9–89 participated in the study. Results: We focused on eight food categories and compared their estimated amounts (using the 24-hour recall method) to those actually consumed (using FW). Animal products and sweets were underestimated, whereas pasta, bread, vegetables, fruits, and dairy products were overestimated. However, the difference between the two methods is not statistically significant except for pasta ( p <0.05) and dairy products ( p <0.05). The coefficient of correlation between the two methods is highly significant, ranging from 0.876 for pasta to 0.989 for dairy products. Nutrient intake calculated for both methods showed insignificant differences except for fat ( p <0.001) and dietary fiber ( p <0.05). A highly significant correlation was observed between the two methods for all micronutrients. The test agreement highlights the lack of difference between the two methods. Conclusion: The difference between the 24-hour recall method using digital photos and the weighing method is acceptable. Our findings indicate that the food photography manual can be a useful tool for quantifying food portion sizes in epidemiological dietary surveys.